The Impact of Organizational Justice on the Organizational Behavior of Generation Z Employees: A Systematic Literature Review - Vini Nur Rindah Arifin; Dina Tri Kusuma Dewi; Shilfi Izzati Munayya (unprimdn.ac.id, 2026)
The current global workforce transition is dominated by Generation Z, who place a high value on transparency and ethical values in the workplace. This study aims to map the impact of organizational justice on the organizational behavior of Generation Z employees to address the limitations of systematic reviews in recent years. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol through an analysis of 16 empirical articles published between 2021 and 2026. The results of the review indicate that organizational justice is a driver of innovative work behavior, affective commitment, and increased organizational trust. In general, it was found that the dimensions of interpersonal justice and procedural transparency have a greater influence than material compensation for Generation Z. Effective organizational justice has been shown to suppress the phenomenon of quiet quitting and reduce the resignation rate (turnover). These findings provide value for human resource management in designing fair and transparent policies to increase employee engagement and long-term organizational stability.